The stranger in the lifeboat : a novel - Albom, Mitch (New York : Harper, 2022)
Adrift in a raft after a deadly ship explosion, nine people struggle for survival at sea. Three days pass. Short on water, food and hope, they spot a man floating in the waves and pull him in. The man, strange and quiet, claims to be the Lord. Is the man who he claims to be? What actually caused the explosion? Are the survivors already in heaven, or are they in hell? Years later, when the empty life raft washes up on the island of Montserrat-- the events recounted in a notebook-- it falls to the island's chief inspector to solve the mystery of what really happened.
Keywords: Shipwreck survival -- Fiction; Religious fiction